2017
DOI: 10.3906/yer-1706-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Moho depth, Curie Point, and heat flow variations of the Yozgat Batholith and its surrounding area, north central Anatolia,Turkey, using gravity and magnetic anomalies

Abstract: This paper proposes an interpretation of the Bouguer gravity and magnetic anomaly map of the Yozgat Batholith and its surrounding area (north central Anatolia) for determination of crustal and geothermal structures. In the study area, the Moho and Conrad depths based on a relationship between Bouguer gravity anomaly and seismically determined crustal thickness were estimated as 34-39 km and 19.5-21.5 km, respectively. The crustal thickness of the study area increases from west to east. The estimated Curie poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Billim et al (2016) suggested that areas with CPD shallower than Moho depth are mostly located in the upper crust. Hence, the magnetic sources in the study area are located in the upper crust which agree with earlier assertions of Billim et al (2016); Billim (2017). Based on the current literatures it could be said that the variation of CPD within the Earth crust is largely depending on the geologic settings of an area.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Billim et al (2016) suggested that areas with CPD shallower than Moho depth are mostly located in the upper crust. Hence, the magnetic sources in the study area are located in the upper crust which agree with earlier assertions of Billim et al (2016); Billim (2017). Based on the current literatures it could be said that the variation of CPD within the Earth crust is largely depending on the geologic settings of an area.…”
Section: Resultssupporting
confidence: 88%
“…The Curie point depth is the depths at which subsurface temperature (approximately 580 o C) loses spontaneous magnetization within the rock units and magnetic minerals show features of paramagnetic susceptibility (Khojamli et al, 2016). The depth at which the temperature reaches the Curie point is known as the Curie point depth (Billim, 2017). Curie point temperatures are not the same, the variation of the temperature depends upon the region, geology, and geochemical rock constituents (Khojamli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%